2016
DOI: 10.1556/0806.44.2016.005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the grain-filling process and starch accumulation of high-yield common buckwheat ‘cv. Fengtian 1’ and tartary buckwheat ‘cv. Jingqiao 2’

Abstract: High-yield common buckwheat 'cv. Fengtian 1' (FT1) and tartary buckwheat 'cv. Jingqiao 2' (JQ2) were selected to investigate the characteristics of the grain-filling process and starch accumulation of high-yield buckwheat. FT1 had an average yield that was 43.0% higher than that of the control 'cv. Tongliaobendixiaoli' (TLBDXL) in two growing seasons, while JQ2 had an average yield that was 27.3% higher than that of the control 'cv. Chuanqiao 2' (CQ2). The Richards equation was utilized to evaluate the grain-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…Dried grains were weighed to calculate the average dry weight of 100 grains. In accordance with the studies of Liang et al [17] and Wang et al [18], Richards' equation was used to describe the grainfilling process:…”
Section: Determination Of Grain Filling Simulationmentioning
confidence: 99%
“…Dried grains were weighed to calculate the average dry weight of 100 grains. In accordance with the studies of Liang et al [17] and Wang et al [18], Richards' equation was used to describe the grainfilling process:…”
Section: Determination Of Grain Filling Simulationmentioning
confidence: 99%
“…The high-yield breeding work of Tartary buckwheat has been focused in China only for a few years [21]. The thick shell Tartary buckwheat 'JQ2' has been proved as a high yield cultivar for planting in Guizhou Province [16]. In this study, the thin shell rice-Tartary buckwheat 'XMQ' showed significant lower yield than JQ2 in two test years.…”
Section: Yield Assessment For Improvement Of Rice-tartary Buckwheatmentioning
confidence: 84%
“…A 100 mg of sample was eluted to remove soluble sugars for three times using 2 mL of 95% ethanol for assay of starch. The details for amylose and amylopectin measurement were performed according to the methods of Liang [16]. Starch content was calculated by amylose content plus amylopectin content.…”
Section: Experimental Methods 231 Assay Of Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1000-grain weight was determined from 10 plants randomly sampled from each plot (thrice the average replicate, with a relative error of <0.5 g for each replicate). Based on the studies of Liang et al (2016) and Wang etal. (2017), Richards' equation was used to describe the grain filling:…”
Section: Methodsmentioning
confidence: 99%